Ionotropic Glutamate Receptors in Hypothalamic Paraventricular and Supraoptic Nuclei Mediate Vasopressin and Oxytocin Release in Unanesthetized Rats - Busnardo, Cristiane; Crestani, Carlos Cesar [UNESP]; Resstel, Leonardo B. M.; Tavares, Rodrigo F.; Antunes-Rodrigues, Jose; Correa, Fernando M. A. (Endocrine Soc, 2012)
We report changes in plasma arginine vasopressin (AVP) and oxytocin (OT) concentrations evoked by the microinjection of L-glutamate (L-glu) into the hypothalamic supraoptic nucleus (SON) and paraventricular nucleus(PVN) of unanesthetized rats, as well as which local mechanisms are involved in their mediation. L-Glu microinjection (10 nmol/100 nl) into the SON increased the circulating levels of both AVP and OT. The AVP increases were blocked by local pretreatment with the selective non-N-methyl-D-aspartate (NMDA) receptor antagonist 2,3-dioxo-6-nitro-1,2,3,4-tetrahydrobenzo[f]quinoxaline-7-sulfonamide (NBQX) (2 nmol/100 nl), but it was not affected by pretreatment with the NMDA-receptor antagonist LY235959 (2 nmol/100 nl). The OT response to L-glu microinjection into the SON was blocked by local pretreatment with either NBQX or LY235959. Furthermore, the administration of either the non-NMDA receptor agonist (+/-)-alpha-amino-3-hydroxy-5-methylisoxazole-4-propionic acid hydrobromide (AMPA) (5 nmol/100 nl) or NMDA receptor agonist NMDA (5 nmol/100 nl) into the SON had no effect on OT baseline plasma levels, but when both agonists were microinjected together these levels were increased. L-Glu microinjection into the PVN did not change circulating levels of either AVP or OT. However, after local pretreatment with LY235959, the L-glu microinjection increased plasma levels of the hormones. The L-glu microinjection into the PVN after the local treatment with NBQX did not affect the circulating AVP and OT levels. Therefore, results suggest the AVP release from the SON is mediated by activation of non-NMDA glutamate receptors, whereas the OT release from this nucleus is mediated by an interaction of NMDA and non-NMDA receptors. The present study also suggests an inhibitory role for NMDA receptors in the PVN on the release of AVP and OT. (Endocrinology 153: 2323-2331, 2012)